Determinants and willingness to practice obstetric analgesia among women attending antenatal clinic at Dr. Bogalech Gebre Memorial General Hospital Central Ethiopia: a cross-sectional study - Teketel Ermias Geltore; Getachew Alemu; Ayanos Taye; Eden Sileshi; Merkin Bekele; Lakew Lafebo Foto (BMC, 2024)
Abstract Background Labor pain is uniquely experienced and described by the woman giving birth, and it is often considered one of the most excruciating experiences for many women. This study aimed to evaluate factors associated with the willingness to receive labor analgesia among women attending the antenatal clinic at Dr. Bogalech Gebre Memorial General Hospital Central Ethiopia in 2022. Methods An institution-based, cross-sectional study was conducted from January to March 2022. Data were collected using semi-structured questionnaires by a convenience sampling technique. Data was entered in EpiData 4.2 and exported to SPSS version 20 for analysis. Both Bivariable and multivariable logistic regressions were conducted to determine factors associated with pregnant women's willingness to choose labor analgesia. Crude odds ratio (COR) and adjusted odds ratio (AOR) were computed to assess the association between variables. Results A total of 398 pregnant women have participated in the study with a response rate of 94%. Nearly 30%, (29.4%) of the pregnant women had a willingness to practice labor pain management. Being a housewife (AOR: 8.35, 95% CI: 2.07, 33.63). Women who live in urban (AOR: 2.60, 95% CI: 1.29, 5.29). Having had awareness about labor analgesia (AOR: 1.70, 95% CI: 1.00, 2.60) and the short duration of labor time (AOR: 1.84, 95% CI: 1.15, 2.96) were statistically significant with a willingness to practice labor analgesia. Conclusion We conclude that the willingness of pregnant mothers' toward obstetric analgesia practice was low in the study area. Being a housewife, urban residence, awareness about labor analgesia, and short duration of labor were statistically significant with the willingness of the mothers to practice labor analgesia. To increase willingness to use labor analgesia, authorities should prioritize delivering health education on pain management choices to address concerns and promote effective methods and practices.